Peran Guru Pendidikan Agama Islam Sebagai Motivator dalam Membentuk Karakter Religius Siswa di Era Digital: Sebuah Kajian Pustaka - Risalatul Mu'awanah; Fatimah Nur Isnaini; Meisa Candra Charisma; Fathonah Septiani Nur Ridha (Prodi Pendidikan Agama Islam IAINU Kebumen, 2026)
The advancement of the digital era has brought significant changes to the field of education, particularly in the development of students’ religious character. While digital progress offers various benefits, it also presents challenges that may influence students’ moral and religious values. In this context, Islamic Religious Education (PAI) teachers carry a vital responsibility in guiding students toward positive character formation. This study aims to analyze the role of PAI teachers as motivators in shaping students’ religious character in the digital era. The researcher adopts a qualitative approach through library research. The findings reveal that the formation of religious character is strongly supported by the strategic role of PAI teachers as mentors, role models, motivators, and sources of inspiration. These roles are carried out through exemplary conduct, habituation of religious practices, moral guidance, and the integration of moral values within the learning process. Nevertheless, PAI teachers face several challenges, including limited digital competence, unequal access to technological infrastructure, curriculum changes, and difficulties in integrating religious values with technological development. Therefore, collaboration among teachers, schools, parents, communities, and the government is essential to strengthen Islamic Religious Education that is relevant, effective, and oriented toward the development of students’ religious character in the digital era